2019
DOI: 10.1111/hae.13652
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor VIII is vital for increasing global coagulation after physical exercise

Abstract: Background In a previous smaller study, we found evidence of a diminished global coagulation capacity after maximal exercise in patients with severe haemophilia A (HA). Aim To validate these results, we repeated the study in a larger cohort. We also examined if the exercise‐induced increased levels of von Willebrand factor (VWF) might prolong the effect of factor concentrate administered just before exercise. Methods We studied individual and global coagulation parameters after maximal physical exercise in 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A study investigating the effects of strenuous exercise on haemostasis found strenuous exercise to increase endothelial activation leading to an increase in vWF plasma levels (83). This study, together with other cross-sectional studies reported that excessive physical activity has a pro-thrombotic effect by increasing plasma levels of FVIII and vWF, platelet reactivity, and activation of the immune system (84)(85)(86)(87). Other studies have yielded conflicting results, and this may have been due to variation in the methodology used, type of exercise, intensity, duration and the population studied.…”
Section: Physical Activitymentioning
confidence: 66%
“…A study investigating the effects of strenuous exercise on haemostasis found strenuous exercise to increase endothelial activation leading to an increase in vWF plasma levels (83). This study, together with other cross-sectional studies reported that excessive physical activity has a pro-thrombotic effect by increasing plasma levels of FVIII and vWF, platelet reactivity, and activation of the immune system (84)(85)(86)(87). Other studies have yielded conflicting results, and this may have been due to variation in the methodology used, type of exercise, intensity, duration and the population studied.…”
Section: Physical Activitymentioning
confidence: 66%
“…In P1, however, the concentration was obtained in most animals after two to three attempts, and in P2, it was obtained always at first. Moreover, the mean platelet count obtained in P2 was higher than in P1, and even within the controversial range (5.16 times above baseline), there is dilution possibility, final platelet concentration adjustment, and PRP use from platelet-poor plasma (PPP) (Fusegawa, Goto, Handa, Kawada, & Ando, 1999;Cattaneo, Lecchi, Zighetti, & Lussana, 2007;Ljungkvist, Olofsson, Funding, Berntorp, & Zetterberg, 2019), while nonconcentrated P1 samples had to be discarded.…”
Section: Resultsmentioning
confidence: 97%
“…In subjects with severe hemophilia A, FVIII release is obtunded, and peak thrombin generation (TG) remains low and unchanged, while TG peak is enhanced in control individuals after exercise. 25 The correlation between stress level and FVIII/VWF release has also been demonstrated between high-dose (presumably stress-free) and low-dose fentanyl anesthesia for cardiac surgical patients. 27…”
Section: Systemic Increases Of Fviii and Vwf In Acute Stressmentioning
confidence: 95%
“…A moderate but transient physical exercise (~15 minutes) elevates circulating epinephrine levels, which mediates a systemic release of FVIII/VWF in healthy individuals. 25,26 Activated partial thromboplastin time (aPTT) is shortened (23 seconds versus baseline 27 seconds) at 10 minutes postexercise, while prothrombin time (PT) does not change. In subjects with severe hemophilia A, FVIII release is obtunded, and peak thrombin generation (TG) remains low and unchanged, while TG peak is enhanced in control individuals after exercise.…”
Section: Systemic Increases Of Fviii and Vwf In Acute Stressmentioning
confidence: 99%
See 1 more Smart Citation